Identifikasi Kesulitan Mahasiswa dalam Penyelesaian Tugas Studio Perancangan Arsitektur Berdasarkan Tingkat Semester - Raihan, Muhammad; Kusuma, Hanson Endra; ZR, Dewi Larasati (Universitas muhammadiyah palembang, 2023)
In the architectural education curriculum, the acquisition of student competencies is facilitated through the engagement in architectural design studio courses. These courses are structured in a sequential manner over the study period. The architectural design studio, constituting a fundamental component of the curriculum, imparts design lessons through practical application, addressing varying project scales and complexities in each semester progressively. Given its central role, the architectural design studio course carries a substantial credit load, surpassing that of other courses in Architectural Education. Consequently, architectural students allocate a significant portion of their study period to studio-based activities. Recognizing the diversity in the scale and complexity of these studios, students encounter a spectrum of experiences and challenges throughout the studio process. This paper aims to identify common problem factors experienced by architecture students during the execution of architectural design studio projects. The insights gathered from this research serve as valuable input for refining the organization and structure of architecture studios. Employing a mixed-method approach, combining qualitative and quantitative research methods, data was collected through online surveys utilizing both open-ended and closed-ended questionnaires. The analysis of the results illuminates the recurring challenges faced by students at different semester levels in completing studio assignments, accompanied by discussions on strategies to address these challenges.